أثر تطبيق بيع المرابحة للآمر بالشراء على تحسين مستوى أداء العاملين في المصارف الليبية - المكاشفي الخضر الطاهر; بشير امحمد الشياني; البصيري البشير القدافي (Surman Journal of Science and Technology, 2024)
The study aimed to explore the impact of implementing Murabaha to the Purchase Ordered on improving employee performance in Libyan banks. It focused on understanding the relationship between the use of this Islamic financing tool and employee performance in terms of efficiency, productivity, and job satisfaction. The study also sought to evaluate employee perceptions of this application to identify the associated challenges and benefits, aiming to provide practical recommendations for enhancing job performance when using Islamic financing products. Data were collected using a questionnaire distributed to 53 employees in banks operating in the Al-Jufra region and analyzed using SPSS software. The results revealed that Murabaha to the Purchase Ordered contributes to improving job performance by increasing employee efficiency and motivating productivity. However, the study highlighted the presence of challenges related to operational and organizational procedures that may affect the effectiveness of its application. The findings also demonstrated the need for banks to enhance their employees' understanding of the Murabaha concept through specialized training programs. The study emphasized the importance of developing internal policies and procedures to ensure the smooth and flexible implementation of such financial products. Additionally, it underlined the necessity of improving communication channels between management and employees to raise awareness of the objectives and benefits of this financial tool. The study concluded that applying Murabaha to the Purchase Ordered can have a tangible positive impact on employee performance in Libyan banks, provided the associated challenges are addressed through employee training, improved organizational procedures, and the development of strategies aimed at enhancing employee understanding and motivation.